ChemInform Abstract: A Convenient Palladium‐Catalyzed Azaindole Synthesis. Issue 24 (June 2015) - De Gasparo, Raoul; Lustenberger, Philipp; Mathes, Chrisitan; Schlama, Thierry; Veitch, Gemma E.; Le Paih, Jaques J. M.
Abstract: A rapid and convenient method for the synthesis of a wide range of 2‐substituted 7‐azaindole derivatives from methyl ketones and 2‐amino‐3‐halopyridines is given.